The Sufi Thought of Sheikh Abdur Rauf as-Singkili: Reconciling Sharia and Spirituality in Responding to Modern Challenges - El-Karimah, Mia Fitriah; Mubarak, Husni (Journal of Sufism and Psychotherapy, 2025)
Sheikh Abdur Rauf as-Singkili (1615-1693) stands as a pivotal figure in the intellectual history of Islam in the Nusantara, particularly for his masterful synthesis of sharia and Sufism during the theological crises of 17th-century Aceh. This study examines the foundational pillars of as-Singkili's Sufi thought and their enduring relevance for contemporary challenges. Employing a qualitative method with an exploratory-phenomenological approach through library research, this study analyzes primary sources including Tarjuman al-Mustafid and 'Umdat al-Muhtajin, alongside secondary literature on his biography and teachings. The findings reveal that as-Singkili's Sufi framework is anchored in six key pillars: reinterpretation of wujudiyyah affirming God's transcendence; inseparability of sharia and tasawuf as complementary dimensions; the concept of Nur Muhammad as cosmic center; the Seven Ranks systematizing God-creation relationships; dhikr as primary practice of divine awareness; and ethics as manifestation of tawhid in behavior. His integrative model—Sharia → Tariqa → Haqiqa → Ma'rifa—established a middle path (wasatiyyah) that prevented both antinomian mysticism and rigid formalism, shaping the distinctive moderate character of Nusantara Islam. The study demonstrates that as-Singkili's teachings remain urgently relevant for addressing modern challenges including materialism and consumerism, digital-age individualism and cyberbullying, and the need for holistic character education. His emphasis on spiritual balance (zuhud), self-control (mujahadah), divine consciousness (muraqabah), and ethics rooted in tawhid offers practical frameworks for navigating contemporary complexities while maintaining spiritual integrity. As-Singkili thus represents a timeless model of Islamic moderation whose intellectual legacy continues to provide foundations for building a tolerant, spiritually grounded, and ethically engaged Muslim society